Effects of early childhood intervention on fertility and maternal employment: Evidence from a randomized controlled trial - Malte Sandner (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper presents the results of a randomized study of a home visiting program implemented in Germany for low-income, first-time mothers. A major goal of the program is to improve the participants' economic self-sufficiency and family planning. I use administrative data from the German social security system and detailed telephone surveys to examine the effects of the intervention on maternal employment, welfare benefits, and household composition. The study reveals that the intervention unintentionally decreased maternal employment and increased subsequent births. These results contradict those of previous studies from the United States, where home visiting programs successfully increased employment and decreased fertility. Analyzing the reason for the different results, suggests that the program interacts with low employment incentives and generous welfare state arrangements for disadvantaged mothers with young children in Germany.
Keywords: J13; J12; I21; H52; 330; Early Childhood Intervention; Randomized Experiment; Fertility